Вплив на навколишнє природне середовище (НПС) бурових робіт та відходів буріння нафтогазових свердловин - Рикусова, Надія Іванівна (НТУ "ХПІ", 2017)
Розглядається вплив відходів буріння та бурових робіт, що проводяться при облаштуванні свердловині, видобутку нафти та експлуатації нафтогазових свердловин. При оцінюванні екологічної небезпеки процесу буріння свердловин аналізується властивості бурового шламу. Виявлено, що хімічний склад бурового шламу залежить від його мінерального складу і властивостей бурового розчину. Мінералогічний склад бурового шламу визначається літологічним складом порід, які розбурюються, він може змінятись по мірі заглиблення свердловини. Результати досліджень складу відходів буріння можуть використовуватися для їх переробки та раціонального використання.

The influence of waste of drilling and drilling operations, which are carried out during construction of wells, oil production and operation of oil and gas wells, is considered. The result of the study is the proposed options for processing and further use of drill cuttings. The scientific novelty is to identify the impact of liquid drilling waste upon the components of natural environment. Practical significance involves systematization of information on the composition of drilling waste, which is necessary in order to develop a scientifically based approach to their utilization. In assessing the environmental safety of drilling process, properties of drill cuttings are analyzed. It was found out that thechemical composition of drill cuttings depends on its mineral composition and properties of drilling fluid. Mineralogical composition of drill cuttingsis determined by lithological composition of rocks, which are drilled, it can change as the well deepens. The results of the studies of drilling waste composition can be used for its processing and rational use.
Impact of drilling operations and waste of drilling of oil and gas wells upon natural environment
Keywords: буровий шлам; розчин; екологічна небезпека; негативний вплив; drill cuttings; drill fluid; drilling waste